INDONESIA-FRANCE DEFENCE COOPERATION: STRENGTHENING NAVAL POWER WITH SCORPENE SUBMARINE AMID REGIONAL DYNAMICS - Ardiansyah, Ruben Firman; Widnyana, I Gede Wahyu; Rofii, Muhammad Syaroni (UI Scholars Hub, 2025)
This study examines Indonesia’s submarine procurement cooperation with France, analysing whether it provides the appropriate amount of power to ensure Indonesia’s survival amid the great power rivalry in the Indo-Pacific region. Using a descriptive qualitative method, the research applies the framework of defensive realism to examine the power to survive. The findings suggest that Indonesia’s choice of the Scorpene-class submarine aligns with its primary security objective. The advanced lithium-ion technology in these submarines offers superior operational endurance and stealth capabilities compared to the conventional submarine technology provided by South Korea and Turkey. The Transfer of Technology (ToT) agreement with France allows Indonesia to reduce reliance on foreign suppliers by building submarines domestically through PT PAL. Furthermore, Indonesia’s submarine possession and future procurement plans are unlikely to disrupt the current distribution of power in the region significantly. By adopting a strategy focused on survival rather than aggression or dominance, Indonesia ensures its sovereignty is protected while avoiding escalating regional conflicts